Parametric Investigation of Oblique Incidence Angle Effects in Near-Fault P Waves on Dynamic Response of Concrete Dam - Shutong Xu; Jiawang Liu; Qiang Xu (Applied Sciences)
Using numerical simulations, this study investigated the seismic response of concrete dams when subjected to near-fault obliquely incident P waves. For comparison, several near-fault pulse-like movements with different motion parameters were selected and decomposed into non-pulse residual components. A seismic input procedure for P wave oblique incidence was developed and verified based on the viscous-spring artificial boundary theory. A finite element model of a concrete dam system was used for nonlinear time history analyses. The damage and displacement responses were analyzed under pulse-like and non-pulse motions with incident angles varying from −90° to 90°. The response differences induced by the pulse characteristics incident direction were examined. The relationship between the seismic parameters and response indices was also determined to obtain the optimal seismic parameter describing the variation under different incident conditions. Moreover, the coupled effect of the pulse feature and oblique incidence on the dynamic response and seismic behavior was examined. Finally, a nonlinear three-dimensional predictive model was proposed based on the optimal seismic parameter Sa(T1) and incident angle, exhibiting high correlation and accuracy. The results demonstrated that incident angles between 60° and 75° (with higher spectral acceleration values) intensified the dam damage and vibration when subjected to the oblique near-fault P waves, a crucial discovery for improving the seismic design and safety measure of concrete dams located in regions prone to near-fault seismic hazards.